TAXONOMIC STUDY FOR THE NEW RECORD OGASTEMMA PUSILLUM (BORAGINACEAE) IN IRAQ - & Shahatha, Mousa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
During the filed survey of   140-160 kilometers region and on both sides of the highway west of Ramadi city in the western desert district of Iraq, and in late spring of 2019, confirmed the recorded of the Ogastemma genus for the first time in Iraq, which was characterized by being a monotypic genus belonging to Boraginaceae family and represented by Ogastemma pusillum. After the identification of the species, which was based on the Flora of the neighboring countries, the species was studied taxonomically. The study worked on describing and photographing all the vegetative and floral parts, anatomy of stem, stomatal complex in leaves, and pollen grains. The plant specimens were preserved under the numbers 60264, 60265 in the Iraqi national herbarium. A morphological study showed that there was uniform indumentum of the epidermis of vegetative organs was appressed-hispid, represented by non-glandular trichomes, medium length of 800-1500 micrometer.